Parental strategies in instilling Islamic values in children: A case study - Chofifah, Nelyn Nur; Lubis, Muhammad Anwar; Anami, Ami Muftil; Hazar, Ibnu; Amirullah; Ash-Shiddiqi, Muhammad Luthfi; Madina, Nazhril Fathra; Faried N, Jung Muhammad; Rahman, Miftahur; Muhammad Ramli; Khairiddin, Fathu; Fasya, Ali; et al. (Research Journal in Advanced Humanities, 2025)
This study explored the strategies employed by parents in Kedurang, Bengkulu Province, to instill Islamic values in their children. Using a qualitative case study approach, the research involved in-depth interviews, participant observation, and document analysis with twelve informants consisting of seven parents and five children. Findings reveal that parents utilized various approaches, including ritual practices, storytelling, ethical guidance, habit formation, and role modeling to embed Islamic teachings into daily life. The research underscores the central role of parents as informal educators, highlighting their adaptive strategies in balancing traditional religious values with contemporary challenges. Children responded positively, expressing joy and engagement in religious activities, often reinforced through familial support and social interaction. This study contributes to the growing discourse on moral education by emphasizing the significance of family-based religious upbringing, especially in rural contexts with limited access to formal religious institutions.